2014
DOI: 10.5935/1678-9741.20140047
|View full text |Cite
|
Sign up to set email alerts
|

Pleural subxyphoid drain confers better pulmonary function and clinical outcomes in chronic obstructive pulmonary disease after off-pump coronary artery bypass grafting: a randomized controlled trial

Abstract: ObjectiveTo evaluate the lung function and clinical outcome in severe chronic obstructive pulmonary disease in patients undergoing off-pump coronary artery bypass grafting with left internal thoracic artery graft, comparing the pleural drain insertion in the intercostal versus subxyphoid region.MethodsA randomized controlled trial. Chronic obstructive pulmonary disease patients were randomized into two groups according pleural drain site: II group (n=27) - pleural drain in intercostal space; SI group (n=29) - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
0
11
1
3
Order By: Relevance
“…In previous studies in which spirometers were used as the means of assessing respiratory pressures, it was concluded that insertion of the pleural drain in the subxiphoid position was associated with lower impairment of respiratory muscle strength. 8,15,20 However, in the present study, the pleural drain position was not found to have any significant influence on maximum respiratory pressures.…”
Section: Statistical Analysescontrasting
confidence: 76%
“…In previous studies in which spirometers were used as the means of assessing respiratory pressures, it was concluded that insertion of the pleural drain in the subxiphoid position was associated with lower impairment of respiratory muscle strength. 8,15,20 However, in the present study, the pleural drain position was not found to have any significant influence on maximum respiratory pressures.…”
Section: Statistical Analysescontrasting
confidence: 76%
“…It is considered a multidimensional syndrome resulting from the reduction of physiological reserves and an increase in physical and functional decline when exposed to external stressors 16 . After cardiac surgery, factors such as cardiopulmonary bypass, surgical incision, pleurotomy and duration of mechanical ventilation generate pulmonary dysfunction and decrease in physiological reserves 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Em todos os estudos que avaliaram a função pulmonar foi utilizada a espirometria, com as medidas de capacidade vital forçada (CVF) e volume expiratório forçado no primeiro segundo (VEF1) (Guizilini, Alves, et al, 2014;Guizilini, Viceconte, et al, 2014;Hagl et al, 1999;Vieira et al, 2012). Dois estudos avaliaram força muscular respiratória pelas medidas de pressão inspiratória máxima (Pimáx) e pressão expiratória máxima (Pemáx), obtidas por manovacuometria (Cancio et al, 2012;Simon et al, 2019).…”
Section: Medidas De Desfechounclassified